Perlindungan Hukum terhadap Hak Kepemilikan Objek Jaminan Fidusia yang telah dialihkan Tanpa sepengetahuan Kreditur - Semuel Willem Simaela; Jenny Kristiana Matuankotta; Sarah Selfina Kuahaty (Faculty of Law, Universitas Pattimura, 2023)
Introduction: The transfer of a fiduciary guarantee must obtain approval from the Fiduciary Giver (Debtor) and the Fiduciary Recipient (Creditor) but in reality there is often a transfer process by the Fiduciary Giver to the buyer who is the third person which is carried out without the knowledge of the Fiduciary recipient (Creditor).Purposes of the Research: The purpose of this paper is to find out and analyze the Legal Protection of Ownership Rights of Fiduciary Guarantee Objects that have been transferred without the knowledge of the creditor. Methods of the Research: The research method used is normative juridical research, the type of research is descriptive analytical. The sources of legal materials used are primary, secondary and tertiary legal materials. The technique of collecting legal materials used in this research is through literature study. The analysis of legal materials is descriptive qualitative.Results of the Research: The results showed that: 1). Legal protection for third parties who have received ownership rights over the object of fiduciary security carried out by the fiduciary giver (debtor) without the knowledge of the fiduciary guarantee recipient (creditor) has never been regulated in the Fiduciary Law. 2). As explained in Pasal 19, Pasal 21 ayat 1, 2, 3, and 4, Pasal 24 and Pasal 25 of the Fiduciary Law that payments for installments on the object of fiduciary security that have been transferred by the fiduciary guarantee provider (debtor) to a third party are made without the knowledge of the fiduciary recipient (creditor) is still part of the debtor's obligation to pay off the installments of the fiduciary guarantee